Daptomycin Plus Fosfomycin Versus Daptomycin Alone for Methicillin-resistant Staphylococcus aureus Bacteremia and Endocarditis: A Randomized Clinical Trial. (29th July 2020) - Pujol, Miquel; Miró, José-María; Shaw, Evelyn; Aguado, Jose-María; San-Juan, Rafael; Puig-Asensio, Mireia; Pigrau, Carles; Calbo, Esther; Montejo, Miguel; Rodriguez-Álvarez, Regino; Garcia-Pais, María-Jose; Pintado, Vicente; et al.
Abstract: Background: We aimed to determine whether daptomycin plus fosfomycin provides higher treatment success than daptomycin alone for methicillin-resistant Staphylococcus aureus (MRSA) bacteremia and endocarditis. Methods: A randomized (1:1) phase 3 superiority, open-label, and parallel group clinical trial of adult inpatients with MRSA bacteremia was conducted at 18 Spanish hospitals. Patients were randomly assigned to receive either 10 mg/kg of daptomycin intravenously daily plus 2 g of fosfomycin intravenously every 6 hours, or 10 mg/kg of daptomycin intravenously daily. Primary endpoint was treatment success 6 weeks after the end of therapy. Results: Of 167 patients randomized, 155 completed the trial and were assessed for the primary endpoint. Treatment success at 6 weeks after the end of therapy was achieved in 40 of 74 patients who received daptomycin plus fosfomycin and in 34 of 81 patients who were given daptomycin alone (54.1% vs 42.0%; relative risk, 1.29 [95% confidence interval, .93–1.8]; P = .135). At 6 weeks, daptomycin plus fosfomycin was associated with lower microbiologic failure (0 vs 9 patients; P = .003) and lower complicated bacteremia (16.2% vs 32.1%; P = .022). Adverse events leading to treatment discontinuation occurred in 13 of 74 patients (17.6%) receiving daptomycin plus fosfomycin, and in 4 of 81 patients (4.9%) receiving daptomycin alone ( P = .018). Conclusions: Daptomycin plus fosfomycin provided 12% higher rate of treatment success than daptomycin alone, but this difference did not reach statistical significance. This antibiotic combination prevented microbiological failure and complicated bacteremia, but it was more often associated with adverse events. Clinical Trials Registration: NCT01898338. Abstract : In this open-label, multicenter, randomized clinical trial, daptomycin plus fosfomycin provided 12% higher rate of treatment success than daptomycin alone at 6 weeks after the end of therapy, but this difference did not reach statistical significance.